Old schools : modernism, education, and the critique of progress - McGlazer, Ramsey (Lit z., 2020)
Old Schools marks out a modernist countertradition: a series of engagements with classical education after the rise of progressive pedagogical theories. The book shows how figures in various cultural vanguards, from Victorian Britain to 1970s Brazil, reimagined the old school to make it facilitate the change it seemed to impede.